Taxonomy of Ophiuroidea (Echinonermata) from the continental shelf and slope of the southern and southeastern Brazilian coast - Borges, Michela; Monteiro, Ana Maria Gouveia [UNESP]; Amaral, Antonia Cecília Zacagnini (Instituto Virtual da Biodiversidade (BIOTA/FAPESP), 2002)
Este estudo foca os ofiuróides coletados durante o Programa de Avaliação do Potencial Sustentável dos Recursos Vivos da Zona Econômica Exclusiva (REVIZEE), Score Sul/Bentos, nos estados de Rio de Janeiro (Baía de Ilha Grande), São Paulo, Paraná, Santa Catarina e Rio Grande do Sul (Tramandaí) (24° 07.113' S e 29° 48.500' S; e 43° 46.759' W e 49° 06.800' W). As amostras foram coletadas na plataforma e talude continental (60-810 m de profundidade) usando os seguintes equipamentos: van Veen, box corer e uma draga retangular. Os indivíduos foram identificados, medidos e fotografados em um estereomicroscópio e um microscópio eletrônico de varredura. Séries de crescimento das espécies com mais de 10 exemplares foram analisadas. do total de 5044 indivíduos, foram identificadas e descritas 29 espécies pertencentes a sete famílias, sendo que as mais abundantes foram Ophiura ljungmani e Ophiomisidium pulchellum, representando 79,7 % do total amostrado. A análise e descrição das espécies assim como a organização das séries de crescimento, permitiram constatar que algumas estruturas morfológicas utilizadas para a identificação do grupo permanecem inalteradas durante toda vida do organismo, enquanto outras passam por alterações. Foram registradas duas ocorrências novas para a costa brasileira: Ophiostriatus striatus e Amphilimna mirabilis. A fauna de ofiuróides está constituída tanto por espécies com ampla distribuição na costa brasileira, como Ophiothrix angulata e Amphipholis squamata, quanto por aquelas com ocorrência restrita a determinadas regiões, como Ophioleptoplax brasiliana e Nudamphiura carvalhoi. A maioria das espécies foi amostrada dentro dos limites batimétricos já registrados para cada uma delas.

This study focuses on the ophiuroids collected during the Programme of Evaluation of the Living Resources of the Exclusive Economic Zone for the Brazilian coast (REVIZEE), South Score/Benthos, in the states of Rio de Janeiro (Ilha Grande Bay), São Paulo, Paraná, Santa Catarina and Rio Grande do Sul (Tramandaí) (24° 07,113' S and 29° 48,500' S; and 43° 46,759' W and 49° 06,800' W). Samples were collected on the continental shelf and slope (60-810 m) using the following equipment: van Veen, box corer and a rectangular dredge. Individuals were identified, measured and photo-graphed under a stereomicroscope and a scanning electron microscope. Growth series of the species that contributed with more than 10 individuals were analysed. A total of 5044 individuals were collected and were represented by 29 species, which belonged to seven families. The most abundant species were Ophiura ljungmani and Ophiomisidium pulchellum, which represented 79.7% of the total number of individuals. The analyses and description of species as well as the organization of the growth series allowed the verification that some characteristics of morphological structures used for the identification of the group remain unaltered throughout the life of the organism, whilst others undergo alterations. We recorded two new occurrences for the Brazilian coast: Ophiostriatus striatus and Amphilimna mirabilis. The ophiuroid fauna is composed of species with wide distribution along the Brazilian coast, such as Ophiothrix angulata and Amphipholis squamata, species with occurrence restricted to certain areas, such as Ophioleptoplax brasiliana and Nudamphiura carvalhoi. Most species were collected within the bathymetry limits previously described for them.
Keywords: Taxonomy; Ophiuroidea; Geographical distribution; bathymetric distribution; Brazil; Taxonomia; Ophiuroidea; Distribuição geográfica; batimetria; Brasil